Functional sequence variants of intergenic long non-coding RNA on Chromosome 17q21 are associated with asthma - Liu, Kwei-Yan; Sie, Jia-Jyun; Gao, Yajing; Lo, Yen-Li; Wu, Chao-Chien; Wang, Chin-Chou; Sheu, Chau-Chyun; Lai, Ruay-Sheng; Leung, Sum-Yee; Lin, Chi-Cheng; Wei, Yu-Feng; Lin, Ching-Hsiung; et al. (The European respiratory journal, 2025)
The genetic and molecular basis of asthma remains unclear and its gene-environment interaction is still enigmatic. In the present study, we aimed to identify asthma-causing genetic variants and their interactions with the environment. We performed case-control genome-wide association studies on individuals of Han Chinese descent from the Taiwan biobank (case=4877 and control=(98 218) to identify asthma susceptibility loci, validated in a hospital-based population of subjects (N=2595). The 10- to 15-year exposure of cumulative ambient particulate matter with a diameter of less than 2.5 μm (PM ) and polycyclic aromatic hydrocarbons (PAHs) were assessed for gene-environment relationships. The function of the newly identified long non-coding RNA, and its interaction with PM and PAH exposure were analyzed using RNA immunoprecipitation, RNA pull-down, RT-qPCR, and western blotting. Chromosome 17q12-21 was found to be a significant risk region, encompassing variants of and its neighboring genes, which interacted with increasing exposure to PM and its adsorbed PAHs. The expression of was elevated, correlating with the expression of its neighboring genes, in the peripheral blood of asthmatic individuals compared to that in controls. Unlike non-risk , the risk variant of disrupted the transcriptional suppression of the risk locus its interaction with the transcription insulator, CCCTC-binding factor (CTCF), concomitant with the higher expression levels of neighboring genes in individuals with the risk genotype. An functional variant of lncRNA, lncZPBP2-3, was significantly associated with asthma and inducible by environmental PAH, suggesting a potentially novel genetic and molecular mechanism of asthma.